(untitled) (Revista Iberoamericana de Bioética, 2024)
In an analysis in the light of science, anthropology and bioethics, euthanasia is characterized as a fallacy of a contemporary society that fails to see death as a condition of the living and in which the meaning of suffering collapses. In this sense, what to expect from a Cape Verdean society that may soon be exposed to the proposed laws on euthanasia? The first section is dedicated to the general concepts of euthanasia, and looks at the position of the Catholic Church; and the second section is about the perception of national healthcare professionals, with a questionnaire addressed to healthcare professionals at one of the country’s leading hospitals. It is intended to lead Cape Verdean society to reflection, since the reality of how to live and how to die is based on the central concept of what the human being is.